Advances in Ductile Iron Research: new metallurgical understanding and its technological significance - Sikora, Jorge Antonio (2005)
The present work gives an updated view about important metallurgical concepts, concerning the influence that solidification structure, microsegregation, piece size and austenite characteristics, exert on final microstructure, properties and processing control. The discussions are based on original results obtained by using special experimental techniques developed by the authors. New evidences about the solidification macrostructure, microsegregation patterns and austenite type (recrystallized and non recrystallized), allow a better understanding of the solidification and the solid state transformations taking place in conventional and thin wall ductile iron castings.